A study on employees perception towards E-HRM practices in It sector - Dhanvi Shah; Jaimini Yagnik (Journal of Management and Science, 2024)
The purpose of this study is to investigate and evaluate how workers in the IT industry view electronic human resource management (e-HRM) methods. The majority of employees see e-HRM practices favorably, noting the enhancements in accessibility, efficiency, and openness of HR services. A portion of the workforce, nonetheless, voice qualms about the impersonal aspect of internet contacts and privacy concerns. The journey of IT is far from over. Emerging technologies like quantum computing, edge computing, and AGI hold the potential to drive the next wave of transformation. However, realizing this potential requires addressing the complex social, ethical, and security issues that accompany technological progress. By learning from the past and fostering a collaborative, inclusive approach to innovation, we can harness the power of IT to build a better future for all.